Exogenous dihomo-γ-linolenic acid triggers ferroptosis via ACSL4-mediated lipid metabolic reprogramming in acute myeloid leukemia cells - Xiandong Jiang; Yingying Huang; Xiaoying Hong; Wei Wu; Yanfeng Lin; Liping Lin; Yan Xue; Donghong Lin (Translational Oncology)
Ferroptosis is a novel type of programmed cell death caused by excessive iron-dependent lipid peroxidation. According to various studies, there may be a link between ferroptosis and lipid metabolism. However, few studies have been reported on the lipid metabolism of ferroptosis in acute myeloid leukemia (AML). Here, we analyzed the relationship between lipid metabolism and ferroptosis in AML cells to explore new clinical treatment strategies. This study found that 12 fatty acids were significantly changed in acute myeloid leukemia cell ferroptosis, including dihomo-γ-linolenic acid (DGLA), arachidonic acid (AA), docosahexaenoic acid (DHA), etc. Exogenous DGLA substantially increases the sensitivity to ferroptosis and induces ferroptosis alone in AML cells. In addition, acyl-CoA synthetase long-chain family member 4 (ACSL4) knockout significantly inhibited DGLA-induced AML cells ferroptosis, and ACSL4 regulates DGLA-associated lipid synthesis to affect the sensitivity of AML cells to ferroptosis. Collectively, our studies indicate that a DGLA-enriched diet significantly restricted the growth of leukemia cells as well as induced ferroptosis in vivo.